Two-fluid simulation of moving grate waste incinerator: Comparison of 2D and 3D bed models - Xia, Zihong; Long, Jisheng; Yan, Shuai; Bai, Li; Du, Hailiang; Chen, Caixia (Energy (Oxford), 2021)
CFD-based simulation models of large-scale moving grate combustor for biomass and municipal solid waste are not well established. Although a 3D transient two-fluid model provides dynamic coupling between the fuel bed and the freeboard, simulation of a whole incinerator is extremely computational intensive and difficult for industrial applications. In this paper, an efficient computational method is proposed where a 2D bed model is combined with a 3D steady furnace model. In the new approach, the bed model includes a transient two-fluid simulation using realistic grate geometry cut by the incinerator throat, which includes a dynamic coupling of heat and mass transfers between the fuel bed and the lower combustion chamber. The simulated bedtop profiles are then used as inlet conditions to run a 3D steady simulation of turbulent gas combustion for the whole furnace. The simulation results are validated with our previous 3D transient full-incinerator results (Xia et al., 2020) [1] and on-site measurement data. In addition, effects of particle size, waste throughput, and residence time on the bed incineration performance are investigated. Overall, the current computational method highly promotes the efficiency of modelling industrial moving grate combustors. •An efficient computational method for moving grate incinerators is proposed.•An interactive two-way coupling bed model is realized.•Results are validated by 3D full-incinerator results and on-site measurement data.•Effects of operating parameters on the bed incineration are investigated.•Relative importance to incineration: particle size > residence time > throughout.